Pelaksanaan Inisiasi Menyusu Dini berdasarkan Jenis Persalinan di Indonesia: Analisis SDKI 2017 - Fakhrunnisa Ahmad; Budi Utomo; Noor Aulia Ramadhan (Fakultas Kedokteran, Kesehatan Masyarakat dan Keperawatan UGM, 2021)
Background: Breast milk that comes out for the first time contains highly nutritious colostrum, has antibody, and very suitable food to consume for new born babies. Immediately after the baby was born, the baby is placed on the mother's breast without any hindrance, so the baby can breastfeed in the first hour and get warmth from the mother's body. Some research suggests that breastfeeding immediately after birth can prevent neonatal and infant death.Objective: This research was conducted to see whether the mother's residence, age, number of children, number of antenatal visits, type of childbirth delivery, and the childbirth assistant's affect the implementation of early breastfeeding.Method: This research will use a cross sectional by using the individual data from IDHS year 2017 with a total data sample of 14341.Results and Discussion: After being analysed using complex sample analysis, the analysis result will show the residence place, number of children, antenatal visits, type of childbirth delivery will become the determined factors from early child breastfeeding. It will be seen that the normal type of delivery allows for early breastfeeding initiation to be 3 times greater than labor with cesarean section after being controlled by variables of residence, number of children, and antenatal visits.Conclusion: Maternal age and birth attendants will not influence the occurrence of early initiation of breastfeeding; type of delivery, residence, number of children, and antenatal visits variables are released to early initiation of breastfeeding Keywords: Breastfeeding initiation; type of delivery; SDKI 2017